PENGARUH TERPAAN JINGLE IKLAN COCA-COLA VERSI WAVIN FLAG TERHADAP BRAND IMAGE - Oktavia, Rani (Universitas Prof. Dr. Moestopo (Beragama), 2012)
One of the products that advertise products are Coca Cola, Coca Cola is one of the famous trademark in the world. Much has been done to conduct marketing, including through advertisements on television. In product advertise on television, today included jingles or musical accompaniment that interesting, to increase the attractiveness of the people who see these ads. Departing from this, the authors were interested in conducting research on the influence of Coca Cola jingle for Coca Colas brand image, especially after the World Cup, where Coca Cola was the official sponsor of the tournament. The above research goals is to determine whether or not the influence as well as to determine how much influence exposure Coca Cola jingle version wavin flag against the Coca Cola brand image. This method is quantitative explanatory writing. Where there are two variables in the study. In conducting this study, the authors use the SOR theory, where one can expect or predict a strong link between media messages and audience reaction, the main elements in this theory is the message (stimulus), receiver (organism), and effects (response ). In addition, the authors also use AIDCA theory (Attention, Interest, Desire, Convinction, Action), which explained that in an advertisement must contain the elements - elements contained in AIDCA, in order to succeed to advertise its products. The population in this study were 77 members of the Manchester United fans, United Indonesia Chapter Depok. In data collection techniques, the authors conducted a review of literature and questionnaires, and the data processing is done with SPSS (Statistics Package Social Science). Based on the research that has been done, it is known that the Coca-Cola ad version Wavin Flag well known by the public, and in addition there is the influence of Coca Cola jingle version of Waving Flag of the brand image of Coca Cola, but the results are still relatively low.